Clinical Performance of the Line Immunoassay, Digital Liquid Chip Method, and Chemiluminescent Immunoassay for Detecting Specific Antinuclear Antibodies - Su, Zhenzhen; Wang, Li; Gao, Xuedan; Huang, Zhuochun; Hu, Jing; Yang, Bin (Archives of pathology & laboratory medicine (1976), 2024)
Antinuclear antibodies (ANAs) against certain antigens are useful for identifying autoimmune disorders. Although new solid phase-based immunoassays have been developed for evaluating ANAs, the conventional line immunoassay (LIA) is commonly used in clinical practice. To compare the clinical performance of 2 newly developed methods for detecting specific ANAs with LIA. Six hundred ninety-six serum samples were collected from 559 patients with autoimmune disease (AID) and 137 controls. The samples were screened by using the LIA, digital liquid chip method (DLCM), and chemiluminescent immunoassay (CLIA) for specific ANAs. The agreement across assays and the clinical performance of each assay in diagnosing ANA-associated rheumatic diseases (AARDs) were evaluated. Almost perfect agreement was observed among all assays for anti-centromere protein B (κ = 0.85-0.97), anti-ribosome P (κ = 0.85-0.88), anti-SSA 52 (κ = 0.86-0.89), and anti-SSA 60 (κ = 0.89-0.91); moderate to substantial agreement was detected for the autoantibodies against Sm, Jo-1, ribonucleoprotein, Scl-70, and SSB (κ = 0.55-0.80). LIA exhibited better sensitivity for diagnosing AARDs, while DLCM and CLIA demonstrated higher specificity. In the subset of AIDs, especially systemic lupus erythematosus, antibody positive percentages varied greatly between assays. The 3 assays showed comparable qualitative agreement; however, the standardization of testing for ANAs remains challenging owing to intermanufacturer variations. Moreover, DLCM and CLIA exhibited better specificity in distinguishing non-AID individuals, whereas LIA was more sensitive in diagnosing AARDs.